Pengaruh Pemberian Minyak Daun Cengkeh (Syzgium aromaticum L) terhadap Cita Rasa dan Daya Simpan Olahan Nugget Ayam - Usman, Usman; Musjulianto, Musjulianto (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
This study aimed to determine the effect of clove leaf oil (Syzgium aromaticum L) addition on the flavor and shelf life of chicken nuggets. The experiment was conducted using a Completely Randomized Design (CRD) consisting of four treatments and five replications. The treatments were P0 (without clove leaf oil), P1 (addition of 4 mL clove leaf oil), P2 (8 mL), and P3 (12 mL). The observed parameters included organoleptic evaluation of flavor (aroma, color, texture) and the shelf life of chicken nuggets. Data were analyzed using analysis of variance (ANOVA), and significant differences were further tested using appropriate post-hoc tests. The results showed that clove leaf oil significantly affected the improvement of flavor and shelf life of chicken nuggets. The best treatment was obtained from the addition of 8 mL clove leaf oil, which produced the most preferred aroma and texture as well as a longer shelf life compared to other treatments.